ANALISIS PENENTUAN HARGA POKOK BATIK: TINJAUAN DARI PROGRAM WIRAUSAHA MERDEKA UNIVERSITAS MUHAMMADIYAH SURAKARTA 2023 - Salsabilla, Aulia Zahwa; Sari, Shinta Permata (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Wirausaha Merdeka is a program that aims to provide students with the opportunity to learn and develop entrepreneurial skills outside the scope of lectures. The program held at Universitas Muhammadiyah Surakarta focuses on the batik industry, especially PT. Batik Danar Hadi. This Wirausha Program activity focuses on calculating the cost of goods of one of the products which aims to determine the cost of goods in accordance with PT. Batik Danar Hadi. The method developed in this activity involves the planning stage, calculation stage, and evaluation stage. The planning stage includes data collection, classification, and identification of the cost of goods manufactured, the calculation stage involves the analysis of the cost of goods manufactured and the determination of the selling price, while the evaluation stage aims to determine the calculation of the cost of goods manufactured in accordance with the company's criteria. The results of this activity show that determining the cost of goods manufactured using the variable costing method is recommended for PT. Batik Danar Hadi through the review of the Wirausaha Merdeka Program.